The Effectiveness of Spinal Cord Stimulation for the Treatment of Axial Low Back Pain: A Systematic Review with Narrative Synthesis. Issue 11 (29th May 2020) - Conger, Aaron; Sperry, Beau P; Cheney, Cole W; Burnham, Taylor M; Mahan, Mark A; Onofrei, Ligia V; Cushman, Daniel M; Wagner, Graham E; Shipman, Hank; Teramoto, Masaru; McCormick, Zachary L
Abstract: Objective: Determine the effectiveness of spinal cord stimulation (SCS) for the treatment of axial low back pain (LBP) with or without leg pain. Design: Systematic review. Subjects: Persons aged ≥18 with axial LBP with or without accompanying leg pain. Intervention: Traditional low-frequency, burst, or high-frequency SCS. Comparison: Sham, active standard of care treatment, or none. Outcomes: The primary outcome was ≥50% pain improvement, and the secondary outcome was functional improvement measured six or more months after treatment intervention. Methods: Publications in PubMed, MEDLINE, and Cochrane databases were reviewed through September 19, 2019. Randomized or nonrandomized comparative studies and nonrandomized studies without internal controls were included. The Cochrane Risk of Bias Tool and GRADE system were used to assess individual study characteristics and overall quality. Results: Query identified 262 publications; 17 were suitable for inclusion. For high-frequency SCS, the only level 1 study showed that 79% (95% confidence interval = 70–87%) of patients reported ≥50% pain improvement. For low-frequency SCS, the only level 1 study reported no categorical data for axial LBP-specific outcomes; axial LBP improved by a mean 14 mm on the visual analog scale at six months. Meta-analysis was not performed due to study heterogeneity. Conclusions: According to GRADE, there is low-quality evidence that high-frequency SCS compared with low-frequency SCS is effective in patients with axial LBP with concomitant leg pain. There is very low-quality evidence for low-frequency SCS for the treatment of axial LBP in patients with concomitant leg pain. There is insufficient evidence addressing the effectiveness of burst SCS to apply a GRADE rating.